2012
DOI: 10.1080/02681102.2011.643210
|View full text |Cite
|
Sign up to set email alerts
|

Youth, mobility and mobile phones in Africa: findings from a three-country study

Abstract: (2012) 'Youth, mobility and mobile phones in Africa : ndings from a three-country study.', Information technology for development., 18 (2). pp. 145-162. Further information on publisher's website: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 30 publications
2
89
1
Order By: Relevance
“…With respect to these issues, much has been written on the role of information and communication technologies in Africa with a special focus on factors that affect the spread of mobile coverage and the impact of mobile phone use on pro-poor labour market access, employment creation and health care (Aker, 2008;Bosch, 2009;Brouwer and Brito, 2012;Buys et al, 2009;Lawson-Body et al, 2011;Maranto and Phang, 2010;Porter, 2012;Porter et al, 2012). However, most of these studies did not investigate the perceptions of the subscribers and the premiums they are willing to pay for a sustainable use of the mobile phone as a device to access market information in rural and peri-urban areas.…”
Section: Willingness To Pay For Market Informationmentioning
confidence: 99%
“…With respect to these issues, much has been written on the role of information and communication technologies in Africa with a special focus on factors that affect the spread of mobile coverage and the impact of mobile phone use on pro-poor labour market access, employment creation and health care (Aker, 2008;Bosch, 2009;Brouwer and Brito, 2012;Buys et al, 2009;Lawson-Body et al, 2011;Maranto and Phang, 2010;Porter, 2012;Porter et al, 2012). However, most of these studies did not investigate the perceptions of the subscribers and the premiums they are willing to pay for a sustainable use of the mobile phone as a device to access market information in rural and peri-urban areas.…”
Section: Willingness To Pay For Market Informationmentioning
confidence: 99%
“…Women and their children, however, have continued to play a dominant role in unpaid domestic and intrasettlement head-porterage, often in support of family commercial activities (Porter 2011;Porter et al 2012a). …”
Section: Background: Transport Services Poverty and Growth In Africamentioning
confidence: 99%
“…Work by Porter et al (2012) has similar aims to this thesis. In their study, the authors explored the relationship between young people's use of mobile phones and the impact this has on society.…”
Section: Studies In Developing Countriesmentioning
confidence: 69%
“…(p. 130) Other crucial issues were the cost of mobile devices and access to the Internet. For example, Auld, Snyder, and Henderson (2012) and Porter et al (2012) demonstrated in their Australian and African studies the importance of shared phones and network facilities. Auld et al (2012) investigated how indigenous people in Australia used mobile phones.…”
Section: Studies In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation